Some Considerations on the Phenomenon of Cybercrime - MOISE, Adrian Cristian (Journal of Advanced Research in Law and Economics, 2017)
In an attempt to define cybercrime, an analysis of the notion of cybercrime is carried out in this study, being presented its characteristics, which make it different from the traditional crimes. Also, an analysis of the main classifications of crimes committed in cyberspace as well as the offenders in the virtual space is carried out in this study.